Single layer of graphene/Prussian blue nano-grid as the low-potential biosensors with high electrocatalysis. (1st November 2016) - Li, Linlin; Peng, Jingmeng; Chu, Zhenyu; Jiang, Danfeng; Jin, Wanqin
Abstract: A single-layer nanogrid of thiol graphene/Prussian blue (tG/PB) composite film was constructed to realize the high electrocatalytic biosensing of various physiological substances under the low potential. In order to achieve this architecture, a single layer of deformed polystyrene (PS) beads was first prepared as the template for the PB deposition. The structure of PB film can be well controlled to build a nanogrid with uniform 500 nm cavities by the self-assembly approach. This film can capture the thiol graphene into its nanogrid cavities to form the composite nanostructure via a strong ionic bond between thiol group from the graphene and Au from the substrate. Both electrocatalysis and conductivity of the as-prepared tG/PB film can harvest the remarkable enhancements due to the synergic effects of PB and graphene. As demonstrated, biosensors constructed by this film exhibited the high sensitivities and accuracies in the electrocatalytic oxidation of glucose, lactate and glutamate under the very low potential −0.05 V.